Fine Coal Beneficiation via Air-Dense Medium Fluidized Beds with Improved Magnetite Powders. Issue 1 (2nd January 2016) - Fu, Zhijie; Zhao, Yuemin; Yang, Xuliang; Luo, Zhenfu; Zhao, Jie
Abstract : Dry beneficiation technology of an air-dense medium fluidized bed offers a number of advantages and expands the choices of efficient dry coal cleaning. Recently, the applications of coal beneficiation by the air-dense medium fluidized bed mainly focus on the size fraction of −50 + 6 mm, but it is difficult to separate −6 mm fine coal using the conventional deployment of dense medium. The objective of this study is to expand the lower separation limit of an air-dense medium fluidized bed by using improved magnetite medium. The smaller magnetite powders of narrow size range having lower minimum fluidization velocity could produce a homogeneous gas-solid fluidized bed, which will be in favor of fine coal separation. The experimental results demonstrate that, for −6 + 3 mm fine coal, the tailing product, having the yield, high-ash content, and total sulfur of 34.39%, 70.27%, and 3.42%, respectively, is efficiently removed. Consequently, the clean coal with a yield of 27.33% has a significant reduction of ash content and total sulfur from 45.92% to 31.29% and from 3.02% to 2.57%, respectively, as well as a considerable calorific increment from 3284 Kcal/kg to 4637 Kcal/kg, and the middling product accounted for 38.27% of the feed has a lower ash content of 35.57%. The ash rejection and the combustible recovery are 52.16% and 89.26%, respectively, indicating that −6 + 3 mm fine coal can be effectively separated in an air-dense medium fluidized bed with improved magnetite powders.